(untitled) (International Journal of Innovative Technologies in Economy, 2020)
The collapse of the Soviet empire led countries to gain their independence. Azerbaijan was one of these countries in a country with a very centuries-old history. The Republic of Azerbaijan, which declared its independence in 1991, underwent reforms to restore its economy. The main goal was to change the mechanism of governing the economy left over from Communism. He first signed the Contract of the Century in 1994. At the same time, it stimulated the development of not only economic relations but also international relations. At the same time, the genocide committed by Armenians in 1989 was a great blow to the people of Azerbaijan. It has been 30 years since the occupation of up to 20% of the territory of Azerbaijan and the failure of the Armenians to return the occupied lands. At a time when capitalism is at its peak in the age of globalization, the unexpected COVID-19 virus, which has frightened the whole world, is causing unexpected damage to the world economy. One of them was Azerbaijan. At a time when capitalism is at its peak in the age of globalization, the unexpected COVID-19 virus, which has frightened the whole world, is causing unexpected damage to the world economy. One of them was Azerbaijan. The shrinking of Azerbaijan’s economy to 4% will lead to the development of new reforms in one way or another. Azerbaijan’s economy, based on a market economy, will be hampered by both a pandemic and the fact that the neighboring country is at war. According to forecasts, the country’s economy is expected to shrink by 10%. Azerbaijan’s relations with Poland, one of its main Western allies, are helping both in economic and other terms. Azerbaijan is a country with its products in the European market. Relations with Poland, a key partner, are growing stronger.